2014
DOI: 10.1017/s1478951514000571
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care clients' and caregivers' notion of fear and their strategies for overcoming it

Abstract: The implications of the findings for healthcare professionals are highlighted. The recognition of emotions is embedded in palliative care; healthcare professionals should view the management of emotions as an integral part of professional practice. Addressing fear is essential because unresolved fear can impinge on one's ability to cope. Our paper brings together different perspectives on fear and how vulnerable individuals attempt to cope with it while at the same time providing a view of the challenges confr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…We know that the burden that patients in palliative care feel that they impose on their family caregivers and the duty that family caregivers feel towards the person they care for can make both prioritise each other’s needs over their own. 18 Indeed, studies in palliative care have shown how remaining positive for one another can help both patients and family caregivers adjust to advanced illness 19 and how remaining collectively steadfast in the face of illness is a dimension to caring. 20 However, reciprocal dimensions to support provision between patients and family caregivers are not routinely mapped out.…”
Section: Introductionmentioning
confidence: 99%
“…We know that the burden that patients in palliative care feel that they impose on their family caregivers and the duty that family caregivers feel towards the person they care for can make both prioritise each other’s needs over their own. 18 Indeed, studies in palliative care have shown how remaining positive for one another can help both patients and family caregivers adjust to advanced illness 19 and how remaining collectively steadfast in the face of illness is a dimension to caring. 20 However, reciprocal dimensions to support provision between patients and family caregivers are not routinely mapped out.…”
Section: Introductionmentioning
confidence: 99%
“…My spirituality makes me feel powerful as it gives me strength and courage to persevere in life. (Penman, 2012; Penman & Ellis, 2015). (Barbara)For when I am down and out, I do reiki.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these improvements, however, attention is still needed to address the psychosocial, emotional, and spiritual needs of clients and caregivers (Penman & Ellis, 2015;Steinhauser et al, 2008). These clients and caregivers (referring to informal carers, who can be spouses, family members, and/or close friends) do experience sadness, a normal part of the dying experience, but it has been estimated that 25% of oncology patients will experience severe depressive symptoms, especially for those with advanced disease and greater pain and disability (Chochinov, 2006; K. G. Wilson, Lander, & Chochinov, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that religious support was one of the most common strategies used by parents when dealing with their fears and anxieties. 22,23 Parents could instill hope through a personal relationship with a higher power during times of crises. 24 Nonreligious theistic parents acquire psychological and spiritual comfort through religious explanations of death and religious rituals when faced with death and grieving.…”
Section: What This Study Addsmentioning
confidence: 99%